An Adaptive Rapid Supervision (ARS) Model for Multigrade Classrooms in 3T (Disadvantaged, Frontier, and Outermost) Regions - Sahbana Ridha; Ahmad Suriansyah; Aslamiah (Universitas Kristen Satya Wacana, 2026)
Multigrade classrooms in Indonesia's 3T (Disadvantaged, Frontier, and Outermost) regions face unique pedagogical challenges that require adaptive supervision approaches different from single-grade contexts. This study developed the Adaptive Rapid Supervision (ARS) Model for multigrade classroom learning in 3T regions and assessed its validity, practicality, and initial benefit indications. The research employed an Educational Design Research approach through preliminary, prototype development, and limited trial evaluation stages. The research context was combined grade 3–4 classrooms at SDN Kecil Juhu and SDN Kecil Datar Batung. The ARS product comprises a model document and operational instrument package including brief pre-observation, one-page two-round observation instrument, four-level rubric, work evidence checklist, single-focus coaching guide, and weekly micro follow-up. Validation by two experts using a Likert scale (1–5) showed a mean of 4.26 (very high category). Limited trials across four sessions showed all ARS components were implemented within 23–28 minutes (mean 25.5 minutes). Process indicators showed improvements after micro follow-up: independent class interruptions decreased from a mean of 8 to 4 times per 10 minutes, on-task behavior increased from 62% to 76%, and rotation transitions improved from approximately 3 minutes to 1.5 minutes. Practitioner practicality and teacher acceptance fell in the very high category with means of 4.34 and 4.22 respectively. ARS is assessed as valid, practical, and has potential to strengthen evidence-based supervision in multigrade classrooms in 3T regions.